Nutrition for health and health care - DeBruyne, Linda K.; Pinna, Kathryn (Boston, MA, USA : Cengage, 2020)
Packed with the latest clinical know-how, this resource enables you to leverage the power of diet therapy to make a real impact on patient lives. You'll uncover the science behind macro-nutrients, vitamins, minerals and metabolism, along with the many ways nutrition affects drugs, diseases and the human life cycle. And to support your success, the interactive MindTap platform features nutrition and diet therapy case studies
Overview of Nurtition and Health -- Digestion and Absorption -- Carbohydrates -- Protein -- Energy Balance and Body Composition -- Weight Management -- Vitamins -- Waters and the Minerals -- Nutrtion through the Life Span: Preganancy and Lactation -- Nutrition through Life Span: Infancy, Childhood, and Adolescence -- Nutrition through the Life Span: Later Adulthood -- Nutrition Care and Assessment -- Nutrition Intervention and Diet Drug Interactions -- Enteral and Parenteral Nutrition Support -- Nutritiom in Metabolic and Respiratory Stress -- Nutrition and Upper Gastronintestinal Disorders -- Nutrition and Lower Gastrointestinal Disorders -- Nutrition and Liver Diseases -- Nutrition and Diabestes Mellitus -- Nutrition and Renal Diseases -- Nutrition, Cancer and HIV Infection -- Case Studies
Actually published in 2019
Includes bibliographical references and index
Keywords: Nutrition; Nutritionally induced diseases; Diet therapy; Nutritional Physiological Phenomena; Nutrition Therapy